Implementation of Multicultural Education in Islamic Religious Education Learning to Foster Tolerance and Brotherhood in Junior High School (SMPN) 2 Samarinda - Khairunnisa Hasani; Khojir Khojir; Muhammad Saparuddin; Atik Atun Farida Munawaroh (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This research aims to describe the implementation of multicultural education in Islamic Religious Education (PAI) learning and its role in shaping tolerance and brotherhood attitudes among students at SMP Negeri 2 Samarinda. This study was motivated by the importance of developing religious education that appreciates cultural and religious diversity in Indonesia’s plural society. The study employed a qualitative descriptive approach using observation, interviews, and documentation as data collection techniques. The research subjects included the principal, PAI teacher, and students. The findings reveal that the implementation of multicultural education in PAI learning is carried out through three stages: (1) planning, which integrates multicultural values into learning modules; (2) implementation, which applies active and collaborative learning methods such as group discussions and role-playing; and (3) evaluation, which emphasizes the affective domain through behavioral assessment and reflection. The results indicate an increase in tolerance by 1% and brotherhood by 1.5% among students, showing that multicultural-based PAI learning positively contributes to creating an inclusive, harmonious, and tolerant educational environment.